K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

Sure, let's solve the equation step by step:

Given Equation:

2⋅3x−1+5⋅3x−3=18632⋅3x−1+5⋅3x−3=1863

Step 1: Combine Like Terms

First, combine the terms with 3x3x and the constant terms separately:

(2⋅3x+5⋅3x)+(−1−3)=1863(2⋅3x+5⋅3x)+(−1−3)=1863 7⋅3x−4=18637⋅3x−4=1863

Step 2: Isolate the Exponential Term

Add 4 to both sides of the equation to isolate the term with 3x3x:

7⋅3x=1863+47⋅3x=1863+4 7⋅3x=18677⋅3x=1867

Step 3: Solve for 3x3x

Divide both sides by 7 to solve for 3x3x:

3x=186773x=71867 3x=266.7142857(approximately)3x=266.7142857(approximately)

Step 4: Solve for xx Using Logarithms

To solve for xx, take the logarithm base 3 of both sides:

x=log⁡3(18677)x=log3(71867)

Using the change of base formula or a calculator:

x=ln⁡(18677)ln⁡(3)≈ln⁡(266.7142857)ln⁡(3)≈5.8891.0986≈5.36x=ln(3)ln(71867)≈ln(3)ln(266.7142857)≈1.09865.889≈5.36

Final Answer:

x≈5.36x≈5.36

\(2\cdot3^{x-1}+5\cdot3^{x-3}=1863\)

=>\(2\cdot3^x\cdot\dfrac{1}{3}+5\cdot3^x\cdot\dfrac{1}{27}=1863\)

=>\(3^x\left(\dfrac{2}{3}+\dfrac{5}{27}\right)=1863\)

=>\(3^x\cdot\dfrac{23}{27}=1863\)

=>\(3^x=1863:\dfrac{23}{27}=2187=3^7\)

=>x=7

28 tháng 8 2017

Ta có \(5^5-5^4+5^3=5^3\left(5^2-5+1\right)=5^3.21=5^3.3.7\)

Vì 53.3 là số nguyên nên \(5^3.3.7⋮7\)

Vậy  \(5^5-5^4+5^3⋮7\)

28 tháng 8 2017

c) \(3^{x+3}+3^{x+1}+2^{x+3}+2^{x+2}\)

\(=\left(3^{x+3}+3^{x+1}\right)+\left(2^{x+3}+2^{x+2}\right)\)

\(=3^x\left(3^2+3\right)+2^x\left(2^2+2\right)\)

\(=3^x.12+2^x.6\)

\(=6\left(2.3^x+2^x\right)\)

Vì \(2.3^x+2^x\in Z\)

Nên : \(6\left(2.3^x+2^x\right)⋮6\)

Vậy \(3^{x+3}+3^{x+1}+2^{x+3}+2^{x+2}⋮6\)

29 tháng 8 2017

a) ta có : \(5^5-5^4+5^3=5^3.\left(5^2-5+1\right)=5^3.\left(25-5+1\right)\)

\(5^3.21=5^3.3.7⋮7\) (đpcm)

b) ta có : \(7^6+7^5-7^4=7^4.\left(7^2+7-1\right)=7^4.\left(49+7-1\right)\)

\(=7^4.55=7^4.5.11⋮11\) (đpcm)

c) ta có : \(3^{x+2}-2^{x+3}+3^x-2^{x+1}=3^{x+2}+3^x-2^{x+3}-2^{x+1}\)

\(=3^x\left(3^2+1\right)-2^x\left(2^3+2\right)=3^x.\left(9+1\right)-2^x.\left(8+2\right)\)

\(=3^x.10-2^x.10=10\left(3^x-2^x\right)⋮10\) (đpcm)

d) \(3^{x+3}+3^{x+1}+2^{x+3}+2^{x+2}=3^x.\left(3^3+3\right)+2^x.\left(2^3+2^2\right)\)

\(=3^x.\left(27+3\right)+2^x\left(8+4\right)=3^x.30+2^x.12=6.\left(3^x.5+2^x.2\right)⋮6\) (đpcm)

29 tháng 8 2017

a)Ta có:\(5^5-5^4+5^3=5^3\left(5^2-5+1\right)=5^3.21\)(vì 21 chia hết cho 7)

\(\)\(\RightarrowĐPCM\)

b)Ta có: \(7^6+7^5-7^4⋮11=7^4\left(7^2+7-1\right)=7^4.55⋮11\)

\(\Rightarrowđpcm\)

a) \(-12\left(x-5\right)+7\left(3-x\right)=15\)

\(\Leftrightarrow-12x+60+21-7x=15\)

\(\Leftrightarrow-19x=15-\left(60+21\right)=-66\)

\(\Leftrightarrow x=\frac{-66}{-19}=\frac{66}{19}\)

Vậy : \(x=\frac{66}{19}\)

b) \(-\left(2x-3\right)-4\left(x+1\right)=-7x+3\)

\(\Leftrightarrow-2x+3-4x-4=-7x+3\)

\(\Leftrightarrow-2x-4x+7x=3-3+4\)

\(\Leftrightarrow x=4\)

Vậy : \(x=4\)

c) \(-5.\left(x+\frac{1}{5}\right)-\frac{1}{2}.\left(x-\frac{2}{3}\right)=\frac{3}{2}.\frac{-5}{6}\)

\(\Leftrightarrow-5x-1-\frac{1}{2}x+\frac{1}{3}=-\frac{5}{4}\)

\(\Leftrightarrow-\frac{11}{2}x=-\frac{5}{4}+1-\frac{1}{3}=-\frac{7}{12}\)

\(\Leftrightarrow x=-\frac{7}{12}:\frac{-11}{2}=\frac{7}{66}\)

Vậy : \(x=\frac{7}{66}\)

Câu d) Xíu làm mình bận >>

d) \(x-\left\{\left[-x+\left(x+3\right)\right]\right\}-\left[\left(x+3\right)-\left(x-2\right)\right]=0\)

\(\Leftrightarrow x-\left[-x+x+3\right]-\left[x+3-x+2\right]=0\)

\(\Leftrightarrow x+x-x-3-x-3+x-2=0\)

\(\Leftrightarrow\left(x+x-x-x+x\right)+\left(-3-3-2\right)=0\)

\(\Leftrightarrow x+\left(-8\right)=0\)

\(\Leftrightarrow x=8\)

Vậy : \(x=8\)

P/s : Câu này cần chú ý quy tắc chuyển dấu và quy tắc thực hiện khi có dấu ngoặc nhé !

a: \(\Leftrightarrow\dfrac{7}{2}x-\dfrac{3}{4}=\dfrac{1}{2}x+\dfrac{5}{2}\)

\(\Leftrightarrow3x=\dfrac{5}{2}+\dfrac{3}{4}=\dfrac{10}{4}+\dfrac{3}{4}=\dfrac{13}{4}\)

=>x=13/12

b: \(\Leftrightarrow x\cdot\left(\dfrac{2}{3}-\dfrac{1}{2}\right)=-\dfrac{1}{3}+\dfrac{2}{5}\)

\(\Leftrightarrow x\cdot\dfrac{1}{6}=\dfrac{-5+6}{15}=\dfrac{1}{15}\)

\(\Leftrightarrow x=\dfrac{1}{15}:\dfrac{1}{6}=\dfrac{2}{5}\)

c: \(\Leftrightarrow x\cdot\dfrac{1}{3}+x\cdot\dfrac{2}{5}+\dfrac{2}{5}=0\)

\(\Leftrightarrow x\cdot\dfrac{11}{15}=-\dfrac{2}{5}\)

\(\Leftrightarrow x=-\dfrac{2}{5}:\dfrac{11}{15}=\dfrac{-2}{5}\cdot\dfrac{15}{11}=\dfrac{-30}{55}=\dfrac{-6}{11}\)

d: \(\Leftrightarrow-\dfrac{1}{3}x+\dfrac{1}{2}+\dfrac{2}{3}-x-\dfrac{1}{2}=5\)

\(\Leftrightarrow-\dfrac{4}{3}x+\dfrac{2}{3}=5\)

\(\Leftrightarrow-\dfrac{4}{3}x=5-\dfrac{2}{3}=\dfrac{13}{3}\)

\(\Leftrightarrow x=\dfrac{13}{3}:\dfrac{-4}{3}=\dfrac{-13}{4}\)

e: \(\Leftrightarrow\left(\dfrac{x+2015}{5}+1\right)+\left(\dfrac{x+2016}{4}+1\right)=\left(\dfrac{x+2017}{3}+1\right)+\left(\dfrac{x+2018}{2}+1\right)\)

=>x+2020=0

hay x=-2020

10 tháng 5 2019

What???

11 tháng 5 2019

Nà ní!!!!!!!!!

Bài 1: Thu gọn a) \(\frac{1}{5}x^4y^3-3x^4y^3\) b) \(5x^2y^5-\frac{1}{4}x^2y^5\) c) \(\frac{1}{7}x^2y^3.\left(-\frac{14}{3}xy^2\right)-\frac{1}{2}xy.\left(x^2y^{\text{4}}\right)\) d) \(\left(3xy\right)^2.\left(-\frac{1}{2}x^3y^2\right)\) e) \(-\frac{1}{4}xy^2+\frac{2}{5}x^2y+\frac{1}{2}xy^2-x^2y\) f) \(\frac{1}{2}x^4y.\left(-\frac{2}{3}x^3y^2\right)-\frac{1}{3}x^7y^3\) g) \(\frac{1}{2}x^2y.\left(-10x^3yz^2\right).\frac{1}{4}x^5y^3z\) h)...
Đọc tiếp

Bài 1: Thu gọn

a) \(\frac{1}{5}x^4y^3-3x^4y^3\)

b) \(5x^2y^5-\frac{1}{4}x^2y^5\)

c) \(\frac{1}{7}x^2y^3.\left(-\frac{14}{3}xy^2\right)-\frac{1}{2}xy.\left(x^2y^{\text{4}}\right)\)

d) \(\left(3xy\right)^2.\left(-\frac{1}{2}x^3y^2\right)\)

e) \(-\frac{1}{4}xy^2+\frac{2}{5}x^2y+\frac{1}{2}xy^2-x^2y\)

f) \(\frac{1}{2}x^4y.\left(-\frac{2}{3}x^3y^2\right)-\frac{1}{3}x^7y^3\)

g) \(\frac{1}{2}x^2y.\left(-10x^3yz^2\right).\frac{1}{4}x^5y^3z\)

h) \(4.\left(-\frac{1}{2}x\right)^2-\frac{3}{2}x.\left(-x\right)+\frac{1}{3}x^2\)

i) \(1\frac{2}{3}x^3y.\left(\frac{-1}{2}xy^2\right)^2-\frac{5}{4}.\frac{8}{15}x^3y.\left(-\frac{1}{2}xy^2\right)^2\)

k) \(-\frac{3}{2}xy^2.\left(\frac{3}{4}x^2y\right)^2-\frac{3}{5}xy.\left(-\frac{1}{3}x^4y^3\right)+\left(-x^2y\right)^2.\left(xy\right)^2\)

n) \(-2\frac{1}{5}xy.\left(-5x\right)^2+\frac{3}{4}y.\frac{2}{3}\left(-x^3\right)-\frac{1}{9}.\left(-x\right)^3.\frac{1}{3}y\)

m) \(\left(-\frac{1}{3}xy^2\right)^2.\left(3x^2y\right)^3.\left(-\frac{5}{2}xy^2z^3\right)^{^2}\)

p) \(-2y.\left|2\right|x^4y^5.\left|-\frac{3}{4}\right|x^3y^2z\)

1
26 tháng 7 2019

Bài 1:

a) \(\frac{1}{5}x^4y^3-3x^4y^3\)

= \(\left(\frac{1}{5}-3\right)x^4y^3\)

= \(-\frac{14}{5}x^4y^3.\)

b) \(5x^2y^5-\frac{1}{4}x^2y^5\)

= \(\left(5-\frac{1}{4}\right)x^2y^5\)

= \(\frac{19}{4}x^2y^5.\)

Mình chỉ làm 2 câu thôi nhé, bạn đăng nhiều quá.

Chúc bạn học tốt!

29 tháng 7 2019

cảm ơn nha

chúc bạn học tốt

24 tháng 6 2016

a) \(\left|x-2\right|+\left|x-5\right|=\left|x-2\right|+\left|5-x\right|\ge\left|x-2+5-x\right|=3\)

Dấu''='' xảy ra \(\Leftrightarrow\begin{cases}x-2\ge0\\5-x\le0\end{cases}\)\(\Leftrightarrow\begin{cases}x\ge2\\x\le5\end{cases}\)\(\Leftrightarrow2\le x\le5\)